Hydrolyzed Formula With Reduced Protein Content Supports Adequate Growth: A Randomized Controlled Noninferiority Trial. Issue 5 (May 2018) - Ahrens, Birgit; Hellmuth, Christian; Haiden, Nadja; Olbertz, Dirk; Hamelmann, Eckard; Vusurovic, Milica; Fleddermann, Manja; Roehle, Robert; Knoll, Anette; Koletzko, Berthold; Wahn, Ulrich; Beyer, Kirsten
ABSTRACT: Objective: A high protein content of nonhydrolyzed infant formula exceeding metabolic requirements can induce rapid weight gain and obesity. Hydrolyzed formula with too low protein (LP) content may result in inadequate growth. The aim of this study was to investigate noninferiority of partial and extensively hydrolyzed formulas (pHF, eHF) with lower hydrolyzed protein content than conventionally, regularly used formulas, with or without synbiotics for normal growth of healthy term infants. Methods: In an European multi-center, parallel, prospective, controlled, double-blind trial, 402 formula-fed infants were randomly assigned to four groups: LP-formulas (1.9 g protein/100 kcal) as pHF with or without synbiotics, LP-eHF formula with synbiotics, or regular protein eHF (2.3 g protein/100 kcal). One hundred and one breast-fed infants served as observational reference group. As primary endpoint, noninferiority of daily weight gain during the first 4 months of life was investigated comparing the LP-group to a regular protein eHF group. Results: A comparison of daily weight gain in infants receiving LPpHF (2.15 g/day CI −0.18 to inf.) with infants receiving regular protein eHF showed noninferior weight gain (−3.5 g/day margin; per protocol [PP] population). Noninferiority was also confirmed for the other tested LP formulas. Likewise, analysis of metabolic parameters and plasma amino acid concentrations demonstrated a safe and balanced nutritional composition. Energetic efficiency for growth (weight) was slightly higher in LPeHF and synbiotics compared with LPpHF and synbiotics. Conclusions: All tested hydrolyzed LP formulas allowed normal weight gain without being inferior to regular protein eHF in the first 4 months of life. This trial was registered at clinicaltrials.gov, NCT01143233. Abstract : Supplemental Digital Content is available in the text